DATA MINING GROUPING LOCATIONS OF DRUG USERS BASED ON THEIR ADDICTION LEVEL - Oni, Riyen (Yayasan Bina Internusa Mabarindo, 2023)
The problem that has now been declared a national disaster is the inappropriate and excessive use of drugs. Where this problem is a negative deviation that can be detrimental to the user, society, the State, and all aspects of life. The unfortunate thing is that these drug users are actually people who know the dangers of using these drugs, but for the sake of their lifestyle they are willing to bear all the consequences of using these drugs. By applying 20 alternative data samples of student data and providing a total of 3 clusters, and utilizing 3 main criteria as research in this proposal, the resulting number of cluster 1 is 8 data, cluster 2 is 10 data. And cluster 3 as much as 2 data. This Drug User Data grouping system is designed with the MATLAB application programming language and utilizes the GUI as its interface.